Man and Animal: J. Pieper’s Discussion with J. J. Uexküll, A. Gehlen, and M. Scheler - Kożuchowski, Józef (Sensus Historiae, 2022)
The article considers an issue that sounds more and more problematic today, namely the existence of an essential difference between a man and an animal. The classic position of J. Pieper, who clearly indicated their existential distinctiveness, has been mentioned here. The thinker from Münster outlined his view on this issue primarily in a discussion with three outstanding German anthropologists: J.J. Uexküll, A. Gehlen, and M. Scheler, which took place in the mid-20th century. The article highlights two threads in particular. The first one is to present the content of Pieper’s critical discussion with the three aforementioned anthropologists, developed in the perspective and spirit of the classical thought of Aristotle and especially of St. Thomas Aquinas. At the same time, it allows us to understand how these thinkers see the issue of the existential separateness of man and animal. The second thread, on the other hand, concerns an attempt to indicate the similarity and, at the same time, a certain difference in Pieper’s classical approach to this issue in relation to the vision of Uexküll, Gehlen and Scheler. The conducted analyzes clearly show that on the basis of classical thought, as Pieper convincingly shows, there exists indeed a radical ontic difference (essential difference) between a man and an animal.